Transabdominal Preperitoneal vs Totally Extraperitoneal for Repairing Inguinal Hernia: A Comparative Study of Short-Term Outcomes (Journal of Science and Technology Research, 2026)
Inguinal hernia repair ranks among the most frequently performed surgical operations globally, offering a range of different methods for addressing the condition. Among these, the Transabdominal Preperitoneal (TAPP) and Totally Extraperitoneal (eTEP) methods stand out as minimally invasive options. These techniques have become increasingly preferred for their benefits compared to the conventional open hernia repair approach. This study aims to compare the short-term outcomes of TAPP and eTEP techniques in inguinal hernia repair. This comparative study within the General Surgery Departments of Shaheed Suhrawardy Medical College & Hospital (ShSMCH) and Mugda Medical College & Hospital during July 2022 to June 2023. Fifty patients were selected via purposive sampling, adhering to specific inclusion and exclusion criteria for inguinal hernia repair, and were subsequently divided into two equal groups. The first group of twenty-five patients received treatment through the TAPP technique, while the second group of twenty-five underwent repair using the eTEP method. The assignment to each technique was carried out using a random lottery system. The investigation focused on short-term outcomes such as operative duration, post-surgery pain levels, hospitalization length, immediate complications, and rates of hernia recurrence. Statistical analyses of the results were obtained by using window based computer software devised with Statistical Packages for Social Sciences (SPSS-20). The average duration of surgery for the TAPP technique was recorded at 99.4±9.1 minutes, compared to 94.4±9.9 minutes for the TEP method, with no statistically significant difference observed between the two. Regarding postoperative pain, measured using the Visual Analogue Scale (VAS), TAPP patients reported significantly lower pain scores at all post-surgery intervals: 3.58±0.53 (6 hours), 3.50±0.76 (12 hours), 3.08±0.53 (24 hours), and 3.01±0.15 (48 hours), whereas TEP patients experienced higher scores of 5.57±0.53 (6 hours), 6.35±0.92 (12 hours), 4.82±0.71 (24 hours), and 3.71±0.31 (48 hours), indicating significantly (p